O bullying em publicações acadêmicas brasileiras nas bases de dados Scielo e Capes entre 2008-2018 - Franco, Cassiana Gardini (Universidade Federal de São Carlos, 2020)
This dissertation refers to an investigation developed in the scope of DEFORGES - Group of Studies and Research in School Organization: Democracy, Human Rights and Principals’ development. It was elaborated in order to obtain the title of Master in Education from the Postgraduate Program in Education - UFSCar, in the research line School Education: Theories and Practices, funded by the Coordination for the Improvement of Higher Education Personnel - CAPES. The objective was to understand how Bullying was conceptualized and characterized in Brazilian academic productions from 2008 to 2018. The problem unfolded into two questions: do the results presented in the publications demonstrate that there is an understanding of the concept of Bullying? Is it possible, through the analyzed publications, to understand how Bullying occurs in Brazilian public schools? The methodology was qualitative, exploratory and bibliographic, and the research was developed in two stages. In the first one, through the descriptors school and Bullying, 43 articles were analyzed in journals in the SciELO Brazil database. In the second, a survey was conducted in the CAPES Thesis and Dissertations Catalog, using the descriptor Bullying, in which 623 works were found. After the titles and abstracts exploratory reading of such works, 67 were selected, 54 dissertations and 13 theses, which were considered relevant to answer the research questions. It was possible to understand that Bullying is one of the manifestations of violence in our society and, mainly at schools. Besides, it was evidenced that, to some extent, Bullying has become part of school routines. It was also possible to understand that despite being a widely known problem, there seems to be difficulties in understanding it due to its complexity and pervasiveness.
Bullying in brazilian academic publications in the Scielo and Capes databases between 2008-2018
Keywords: Violência; Escola pública de educação básica; Violence; Public school of basic education; Bullying; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO